High sensitivity and specificity of the Pastorex latex agglutination test for Neisseria meningitidis serogroup A during a clinical trial in Niger. - Borel, T; Rose, A; Guillerm, M; Sidikou, F; Gerstl, S; Djibo, A; Nathan, N; Chanteau, S; Guerin, P (2006)
There is a great need for a rapid diagnostic test to guide vaccine choice during outbreaks of meningococcal meningitis in resource-poor countries. During a randomised clinical trial conducted during an epidemic of Neisseria meningitidis serogroup A in Niger in 2003, the sensitivity and specificity of the Pastorex latex agglutination test for this serogroup under optimal field conditions were assessed, using culture and/or PCR as the gold standard. Results from 484 samples showed a sensitivity of 88% (95% CI 85-91%) and a specificity of 93% (95% CI 90-95%). Pastorex could be a good alternative to current methods, as it can be performed in a local laboratory with rapid results and is highly specific. Sensitivity can be improved with prior microscopy where feasible. A study specifically to evaluate the Pastorex test under epidemic conditions, using laboratories with limited resources, is recommended.